2006
DOI: 10.1002/pssb.200672589
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure properties and phase diagram of boron

Abstract: Phase diagram of boron is theoretically studied, with focusing mainly on difference between α and β phases. The melting curve is calculated by the pressure dependence of the bulk modulus of solid. It is found that the gradient of the melting curve is inverted at a high pressure. Based on this finding, a promising method to obtain good-quality crystals of α phase is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
4
22
0
1
Order By: Relevance
“…Also, high pressure properties and phase diagrams of boron were studied by Shirai et al [61] theoretically, and they discussed pressure-dependence of the properties, and it was reported that ␣-boron was the most stable phase at low temperatures and ␤-boron phase was most favorable phase at high temperatures [17,19,24,61]. On the other hand, using quasi-harmonic approximation [61,62], it was reported high pressure results of experiments and theoretic studies of ␣-and ␤-boron phases to understand of high pressure properties of icosahedrons-based boron phases.…”
Section: Pressure-induced Phase Transitionsmentioning
confidence: 99%
“…Also, high pressure properties and phase diagrams of boron were studied by Shirai et al [61] theoretically, and they discussed pressure-dependence of the properties, and it was reported that ␣-boron was the most stable phase at low temperatures and ␤-boron phase was most favorable phase at high temperatures [17,19,24,61]. On the other hand, using quasi-harmonic approximation [61,62], it was reported high pressure results of experiments and theoretic studies of ␣-and ␤-boron phases to understand of high pressure properties of icosahedrons-based boron phases.…”
Section: Pressure-induced Phase Transitionsmentioning
confidence: 99%
“…Even the phase diagram of elemental boron is still open to question, i.e. the theoretical diagram proposed by Shirai et al [13] contradicts not only the metastability of the rhombohedral α-B 12 phase at ambient pressure [14][15][16], but also the slope of the boron melting curve established in the recovery [17] and in situ [18] experiments.…”
Section: Introductionmentioning
confidence: 96%
“…Characterizing materials from electronic stiffness and internal degree of freedom provides a good guideline for high-pressure material researches. [7,8] and (b) by Oganov [12]. The numbers in Fig.…”
Section: Koun Shiraimentioning
confidence: 96%
“…(a) indicate experimental data, whose sources are described in Ref. [7,8]. 評価される。変形ポテンシャルは a=de/dp である。 バンドエネルギー e としてどれを用いるかによって…”
Section: Koun Shiraiunclassified